2018
DOI: 10.5603/ep.a2018.0026
|View full text |Cite
|
Sign up to set email alerts
|

Ekspresja adiponektyny w otyłości trzewnej jest istotnym wyznacznikiem insulinooporności w otyłości olbrzymiej

Abstract: In severely obese patients, adiponectin gene expression in VAT is negatively correlated with serum levels of uric acid and is an independent determinant, together with anthropometric parameters of visceral obesity and serum adiponectin levels, of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
8
0
3
Order By: Relevance
“…Recent evidence has demonstrated that there are over 50 different adipokines secreted from adipose tissue [48][49][50][51]. The main processes regulated by adipokines may be divided into three groups: 1. lipids and glucose metabolism; 2. inflammatory processes; and 3. blood pressure and haemostasis.…”
Section: Hormonal Activity Of Adipose Tissuesmentioning
confidence: 99%
“…Recent evidence has demonstrated that there are over 50 different adipokines secreted from adipose tissue [48][49][50][51]. The main processes regulated by adipokines may be divided into three groups: 1. lipids and glucose metabolism; 2. inflammatory processes; and 3. blood pressure and haemostasis.…”
Section: Hormonal Activity Of Adipose Tissuesmentioning
confidence: 99%
“…It is worth mentioning that unlike other studies [22], we report higher values in the obese subjects. This finding could sustain that not circulating adiponectin, but the local expression in perivisceral fat and also the distribution of adipose tissue, are related with its metabolic functions [23,24]. An alternative explanation could be the adiponectin resistance phenomena, recently described by Engin [25], as a compensatory response caused by adiponectin unresponsiveness to IR at different stages of obesity.…”
Section: Resultsmentioning
confidence: 68%
“…Obesity is connected with many changes of metabolic parameters. Qualification of patients for bariatric sur- gery must consider the lipid and carbohydrate panels and liver enzymes activity [16]. Analysis of triglycerides showed differences between the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%